1989
DOI: 10.1038/clpt.1989.142
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of viqualine on alcohol intake and other consummatory behaviors

Abstract: Viqualine, a serotonin releaser and uptake inhibitor, was studied for its effects on consummatory behaviors (intake of ethanol and nonalcoholic beverages, cigarette smoking, and changes in body weight) in 29 men who were early-stage problem drinkers between 21 to 55 years of age. Subjects were randomly assigned to receive a placebo and either 100 mg/day viqualine (n = 15) or 200 mg/day viqualine (n = 14) orally in a double-blind crossover study. Viqualine administration and ethanol intake were assessed by self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…The selective serotonin reuptake inhibitors (SSRIs) zimelidine, citalopram, viqualine, and fluoxetine were shown to produce modest decreases in alcohol consumption in nondepressed heavy drinkers (Naranjo et al 1984(Naranjo et al , 1987(Naranjo et al , 1989(Naranjo et al , 1990. However, when fluvoxamine was combined with cognitive-behavioral therapy to treat alcohol dependence, the medication was poorly tolerated and seemed to be unsuitable for use among patients with this disorder (Kranzler et al 1993).…”
mentioning
confidence: 99%
“…The selective serotonin reuptake inhibitors (SSRIs) zimelidine, citalopram, viqualine, and fluoxetine were shown to produce modest decreases in alcohol consumption in nondepressed heavy drinkers (Naranjo et al 1984(Naranjo et al , 1987(Naranjo et al , 1989(Naranjo et al , 1990. However, when fluvoxamine was combined with cognitive-behavioral therapy to treat alcohol dependence, the medication was poorly tolerated and seemed to be unsuitable for use among patients with this disorder (Kranzler et al 1993).…”
mentioning
confidence: 99%
“…On the remaining 3 days of separation, the animals' behaviors were recorded in the morning, prior to alcohol exposure. Plasma sertraline concentrations were quantified at Pfizer laboratories using the method described by Tremaine (Tremaine and Joerg 1989).Preclinical studies suggest that the reduction in alcohol consumption by SSRIs such as sertraline is part of a general pattern of overall reduction in food and liquid intake (Lucki et al 1988;Higgins et al 1992), and in humans, SSRI treatment sometimes produces weight loss (Naranjo et al 1989). To assess the possibility that sertraline produced its effects by simply reducing all consummatory behaviors including alcohol intake, daily food intake and weekly weight were recorded in all subjects.…”
mentioning
confidence: 99%
“…Decreases in desire to drink were also reported in some clinical trials (Amit et al, 1985;Gorelick and Paredes, 1992;Naranjo et al, 1989), leading to the testing of citalopram and fluoxetine in an experimental paradigm designed to assess interest, desire and liking of alcohol. The results indicated that decreases in interest and desire (urge to drink) and liking (reinforcing effects) of alcohol may mediate the effect of serotonin uptake inhibitors (Naranjo el al., 1992a;1992b).…”
Section: Introductionmentioning
confidence: 89%